Identification of Performance Measures for Textile Supply Chain: Case of Small & Medium Size Enterprise - Pranav Gopal Charkha; Santosh B Jaju (International Journal of Supply Chain Management, 2015)
Identifying the performance measures for textile supply chain network is rapidly growing multi criteria decision making problem and so the task of performance measurement due to large number of parameters involvement. Selection analysis of appropriate performance measures is critical to achieve success for textile industry in todays global competitive market. With this paper, we tried to overcome it by recognizing three areas; i) cyclic processes of supply chain network (procurement-production-distribution), ii) measures under three decision making levels iii) considering balanced scorecard (BSC) perspectives Developed a framework for supply chain performance measurement and analyzed using analytical hierarchy process.